Reducing implicit racial preferences: II. Intervention effectiveness across time - Lai, Calvin K; Skinner, Allison L; Cooley, Erin; Murrar, Sohad; Brauer, Markus; Devos, Thierry; Calanchini, Jimmy; Xiao, Y Jenny; Pedram, Christina; Marshburn, Christopher K; Simon, Stefanie; Blanchar, John C; et al. (Journal of experimental psychology. General, 2016)
Implicit preferences are malleable, but does that change last? We tested 9 interventions (8 real and 1 sham) to reduce implicit racial preferences over time. In 2 studies with a total of 6,321 participants, all 9 interventions immediately reduced implicit preferences. However, none were effective after a delay of several hours to several days. We also found that these interventions did not change explicit racial preferences and were not reliably moderated by motivations to respond without prejudice. Short-term malleability in implicit preferences does not necessarily lead to long-term change, raising new questions about the flexibility and stability of implicit preferences. (PsycINFO Database Record